TEACHERS’ STRATEGIES IN TEACHING READING COMPREHENSION TO SEVENTH-GRADE STUDENTS OF SMPN 10 TARAKAN - Abraham, Abraham; Fitriawati, Fitriawati; Kusmaryani, Woro (Universitas Borneo Tarakan, 2023)
This research aims to determine the methods for incorporating reading comprehension skills into classroom instruction and identify the specific strategies teachers employ. This study employs a descriptive qualitative approach. The participants of this study were English instructors at SMP Negeri 10 Tarakan, comprising a single teacher. The primary objective of this study is to examine the instructional techniques teachers employ to enhance reading comprehension skills among students in the classroom setting. The research data collection was conducted through documentation, observation, and interviews. Based on the observations and conversations, the instructor employs two specific strategies: scaffolding and QARs (Question-Answer Relationship).Â